High Availability Routing Protocol for Wsn - Kaschel-Carcamo, H; Viera-Riquelme, E (Institute of Electrical and Electronics Engineers Inc., 2018)
Currently, WSN (Wireless Sensor Networks) have become a relevant topic for researchers in a wide implementation area (Industry, Environment, Medical, etc WSN have interesting features and optimal capabilities in several applications, i.e., applications where it s required to have architecture flexibility, low power consumption, transparent transition mode, etc.From the fault tolerance point of view and network robustness, this research presents an improvement by means of a very simple protocol, managed by the application layer levels (OSI model reference); obtaining electrical and transmission parameters, such as: Current drawn, voltage levels and RSSI (Reception Strength Signal Indicator). © 2018 IEEE.